UNDERSTANDING THE DRIVERS OF ANEMIA AMONG PREGNANT WOMEN: A CROSS-SECTIONAL STUDY: Memahami Faktor-Faktor Penyebab Anemia pada Ibu Hamil: Studi Cross-Sectional - Riaya Fauziah; Erni Gustina; Kania Valentia Febriana; Ardyawati Wira Oktaviana; Yuniar Wardani; Liena Sofiana; Suci Musvita Ayu; Baiq Qatrunnada Hariyanti (Jurnal Berkala Epidemiologi, 2026)
Background: Anemia is a global health issue, particularly among pregnant women in developing countries, with an estimated 35% of pregnant women worldwide expected to be anemic by 2023. This condition increases the risk of complications for both mother and fetus, such as fatigue, preterm birth, and low birth weight. It is influenced by maternal factors, including age, chronic energy deficiency (CED), and educational level. Purpose: This study aims to identify the relationship among maternal age, chronic energy deficiency, education level, and the occurrence of anemia in pregnant women. Methods: This cross-sectional study was conducted in the working area of the Pakuncen Community Health Center and involved 192 pregnant women selected using purposive random sampling. Data were collected using a structured questionnaire to determine the age, educational level, CED, and anemia status. Anemia status was determined by measuring hemoglobin levels using HemoCue, while CED status was assessed by upper-arm circumference (UAC). Data analysis used chi-square tests and logistic regression. Results: The prevalence of anemia was 40.60%. Maternal age, education level, and CED status were significantly associated with anemia incidence (p<0.05). Logistic regression showed that mothers with low education (AOR = 3.41; 95% CI: 1.77-6.53), experiencing CED (AOR = 2.17; 95% CI: 1.12-4.20), and aged <20 or >35 years (AOR = 2.35; 95% CI: 1.18-4.68) had a higher likelihood of anemia. Conclusion: Maternal age, nutritional status, and education level significantly affect anemia risk. Improving nutrition education and supporting empowerment can help reduce anemia and improve the health of mothers and infants.